2011
DOI: 10.3844/ajavsp.2011.80.83
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Polymorphism at the Insulin Like Growth Factor-I Gene in Mazandaran Native Chicken using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism Method

Abstract: Problem statement: Molecular genetics selection on individual genes is a promising method to genetically improve economically important traits in chickens. The Insulin like Growth Factor-I (IGF1) gene may play important roles in growth of multiple tissues, including muscle cells, cartilage and bone. Approach: In the present study polymorphism of the promoter and 5' untranslated region of IGF-1 gene of Mazandaran native fowls was investigated. In order to evaluate the IGF-1 gene polymorphism we have used a Rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…It is demonstrated by the unrestricted fragment using the restriction enzyme Pst1. It is in line with previous results which stated that unrestricted DNA fragments define homozygote alleles (Nagaraja et al 2000;Kim et al 2004;Abbasi and Kazemi 2011;Kadlec et al 2011;Ali et al 2016). It also supported by Mu'in et al (2009), who reported that the restriction enzyme would be unable to cut the DNA fragment within homozygote alleles.…”
Section: Pcr-rflp Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…It is demonstrated by the unrestricted fragment using the restriction enzyme Pst1. It is in line with previous results which stated that unrestricted DNA fragments define homozygote alleles (Nagaraja et al 2000;Kim et al 2004;Abbasi and Kazemi 2011;Kadlec et al 2011;Ali et al 2016). It also supported by Mu'in et al (2009), who reported that the restriction enzyme would be unable to cut the DNA fragment within homozygote alleles.…”
Section: Pcr-rflp Analysissupporting
confidence: 93%
“…IGF-1 has a role in supporting the growth of somatic cells, fibroblasts, muscle, and bone (Abbasi and Kazemi 2011). Therefore, this gene is also involved in chicken growth.…”
Section: Introductionmentioning
confidence: 99%
“…For example, on Ningdu Shanghuang breed, the frequency of C allele was higher than T allele in DRD2/BSeGI mutation point (Xu et al, 2010;Xu et al, 2011a;Xu et al, 2011b). In addition, Kim et al (2004) showed that C allele frequency (0.31) was lower than T allele (0.69) at IGF-I/PstI polymorphic position in Ogol chicken, but on the same Madandaran chicken, the distribution of 2 alleles was relatively equal (0.51 and 0.49) (Abbasi & Kazemi, 2011). In addition, a comparison of allele frequency on VIPR-1/TaqI polymorphism also pointed out that most of the experimental chickens in the population had a higher proportion of C allele.…”
Section: Resultsmentioning
confidence: 96%
“…Nagaraja et al (2000) showed that a PstI RFLP in the 5′ flanking region of the IGF1 gene was associated with egg and egg shell weights in a White Leghorn chicken population. Abbasi and Kazemi (2011) also reported a polymorphism in the 621 bp flanking promoter and 5′ untranslated region in the fowl IGF1 gene and identified two alleles. A HinfI RFLP of a 793 bp fragment of the IGF1 gene was reported to be polymorphic in broiler chickens also indicating the presence of two alleles (Shah et al, 2012).…”
Section: Introductionmentioning
confidence: 92%